Mutations in the Amyloid-β Protein Precursor Reduce Mitochondrial Function and Alter Gene Expression Independent of 42-Residue Amyloid-β Peptide. - Pope, Chad A; Wilkins, Heather M; Swerdlow, Russell H; Wolfe, Michael S (J Alzheimers Dis, 2021)
BACKGROUND: Dominant missense mutations in the amyloid-β protein precursor (AβPP) cause early-onset familial Alzheimer's disease (FAD) and are associated with changes in the production or properties of the amyloid-β peptide (Aβ), particularly of the 42-residue variant (Aβ 42) that deposits in the Alzheimer's disease (AD) brain. Recent findings, however, show that FAD mutations in AβPP also lead to increased production of longer Aβ variants of 45-49 residues in length. OBJECTIVE: We aimed to test neurotoxicity of Aβ 42 vis-á-vis longer variants, focusing specifically on mitochondrial function, as dysfunctional mitochondria are implicated in the pathogenesis of AD. METHODS: We generated SH-SY5Y human neuroblastoma cells stably expressing AβPP mutations that lead to increased production of long Aβ peptides with or without Aβ 42. These AβPP-expressing cells were tested for oxygen consumption rates (OCR) under different conditions designed to interrogate mitochondrial function. These cell lines were also examined for expression of genes important for mitochondrial or neuronal structure and function. RESULTS: The mutant AβPP-expressing cells showed decreased basal OCRs as well as decreased OCRs associated with mitochondrial ATP production, even more so in the absence of Aβ 42 production. Moreover, mutant AβPP-expressing cells producing longer forms of Aβ displayed altered expression of certain mitochondrial- and neuronal-associated genes, whether or not Aβ 42 was produced. CONCLUSION: These findings suggest that mutant AβPP can cause mitochondrial dysfunction that is associated with long Aβ but not with Aβ 42.